Liver cirrhosis prediction for patients with Wilson disease based on machine learning: a case–control study from southwest China. Issue 10 (25th July 2022) - Chen, Ke; Wan, Yang; Mao, Ju; Lai, Yuqing; Zhuo-ma, Gesang; Hong, Peiwei
Abstract : Objectives: Wilson disease (WD) is a rare autosomal recessive disease caused by an ATP7B gene mutation. Liver cirrhosis is an important issue that affects the clinical management and prognosis of WD patients. Blood routine examination is a potential biomarker for predicting the occurrence of liver cirrhosis in WD. We aim to construct a predictive model for the occurrence of liver cirrhosis using general clinical information, blood routine examination, urine copper, and serum ceruloplasmin through a machine learning approach. Methods: Case–control study of WD patients admitted to West China Fourth Hospital between 2005 and 2020. Patients with a score of at least four in scoring system of WD were enrolled. A machine learning model was constructed by EmpowerStats software according to the general clinical data, blood routine examination, 24 h urinary copper, and serum ceruloplasmin. Results: This study analyzed 346 WD patients, of which 246 were without liver cirrhosis. And we found platelet large cell count (P-LCC), red cell distribution width CV (RDW-CV), serum ceruloplasmin, age at diagnosis, and mean corpuscular volume (MCV) were the top five important predictors. Moreover, the model was of high accuracy, with an area under the receiver operating characteristic curve of 0.9998 in the training set and 0.7873 in the testing set. Conclusions: In conclusion, the predictive model for predicting liver cirrhosis in WD, constructed by machine learning, had a higher accuracy. And the most important indices in the predictive model were P-LCC, RDW-CV, serum ceruloplasmin, age at diagnosis, and MCV.